Knowledge and behavior of professionals about bundled strategies of central venous catheter - Bruna Figueiredo Manzo; Danielle Rodrigues Mariano; Fernanda Maria Correa Ferreira; Fernanda Penido Matozinhos; Delma Aurélia da Silva Simão; Anna Caroline Leite Costa; Allana dos Reis Corrêa
ABSTRACT Objective: To investigate the factors that influence the knowledge and behavior of professionals of neonatal and pediatric units about bundled strategies of insertion of central venous catheter. Method: This is a cross-sectional study, conducted in one neonatal and one pediatric intensive care units in a public hospital in Belo Horizonte, Brazil, from April to July, 2016. The sample consisted of 255 professionals who answered a structured instrument. Descriptive and comparative analyses were made using the SPSS software. Results: The category nursing professional (p = 0.010), working hours of 12×36 scale (p < 0.001), training as a form of acquiring knowledge (p < 0.001) and participation in training programs (p < 0.001) are associated to greater knowledge about the bundle. Regarding behavior, no significant associations were observed. Conclusion: The study showed that there are factors that influence the knowledge about bundled strategies of insertion of central venous catheter, reflecting the need to consider these practices for making more effective educational practices in health care.